-30x+12(x-1)=24x+2

Simple and best practice solution for -30x+12(x-1)=24x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -30x+12(x-1)=24x+2 equation:


Simplifying
-30x + 12(x + -1) = 24x + 2

Reorder the terms:
-30x + 12(-1 + x) = 24x + 2
-30x + (-1 * 12 + x * 12) = 24x + 2
-30x + (-12 + 12x) = 24x + 2

Reorder the terms:
-12 + -30x + 12x = 24x + 2

Combine like terms: -30x + 12x = -18x
-12 + -18x = 24x + 2

Reorder the terms:
-12 + -18x = 2 + 24x

Solving
-12 + -18x = 2 + 24x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-24x' to each side of the equation.
-12 + -18x + -24x = 2 + 24x + -24x

Combine like terms: -18x + -24x = -42x
-12 + -42x = 2 + 24x + -24x

Combine like terms: 24x + -24x = 0
-12 + -42x = 2 + 0
-12 + -42x = 2

Add '12' to each side of the equation.
-12 + 12 + -42x = 2 + 12

Combine like terms: -12 + 12 = 0
0 + -42x = 2 + 12
-42x = 2 + 12

Combine like terms: 2 + 12 = 14
-42x = 14

Divide each side by '-42'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 875/x/60=26.25 | | 7x=1/2*105 | | 5x-4=11+2n | | 9(3x-5)+9x= | | 3(x-4)=23-4c | | 3lnc=2lny | | 6+6x-2x=-10 | | 25t^2+45t=0 | | 5log(5x-10)=15 | | 3ln(2X)=27 | | 10(3x+12)+13x-14= | | 3h=-18 | | 48-5x=18 | | 3+4x+5x=48 | | 8(x-9)=15 | | -3+-b=1 | | 2x-(24/x)-8=0 | | x+2y-3=xy | | 15x^2-27y^2=12 | | 4(3x+7)=10 | | 7y+4(y-5)=4(y+1)-2 | | -7r=14 | | 3(5x+9)=37+19 | | x^2-27y^2=12 | | A^2+12a=-32 | | -3=p/6-6 | | 8a+-3=5 | | 3(2x+3)=2x-7 | | 7(4x-6)-7=28x-49 | | ln(x+2)+ln(x+4)=2 | | 3x+5x-4=4 | | 4(5x+6)+2(8-x)= |

Equations solver categories